Determinant of Intimate partner violence Family: parametric Statistics of the influence of household decision-making autonomy and Family Income Status - Ibiam, Azu A.; Anam, Asari E.; Ojong-Ejoh, Mary U.; Enamhe, Dorn Cklaimz; Igwe-Okomiso, Joseph B.; Ejoh, Tabe Ojong (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2021)
The study is an analysis of the relationship between household decision-making autonomy, family income status and intimate partner violence in Calabar South, Cross River State, Nigeria. Adopting the exchange/social control theory, the study applied the survey research design in gathering data from 383 respondents from Calabar South, using a structured interview questionnaire. Elicited data was analyzed using simple lineal regression at 0.05 alpha Level. Result revealed that household decision making autonomy and family income status has significant influence on intimate partner violence in Calabar South Local Government Area The study thereby calls for the development of evidence-based culturally appropriate interventions that address the issue of unequal power relations between men and women